Metaphysical Knowledge - Claudine Tiercelin (Collège de France, 2013)
Metaphysics has been proclaimed to be archaic or outdated. Actually, it never "died". It has even experienced considerable revival throughout the world, which in France we have yet to fully appreciate. Because, in both the most general and the most precise ways, it questions "what there is", it is essential to any knowledge-related undertaking, in the sense not of a recognition of eternal truths but of an enquiry on the world and on reality. In this lecture Claudine Tiercelin sets out the pro...